STRATEGIES FOR ENHANCING TEACHER INNOVATION THROUGH DIGITAL LEADERSHIP, PROFESSIONAL LEARNING COMMUNITY, PROACTIVE PERSONALITY, KNOWLEDGE SHARING, AND CREATIVE SELF-EFFICACY - Ade Setiadi Aulia; Soewarto Hardhienata; Herfina (Program Studi Manajemen Pendidikan Islam, 2026)
Teacher innovation is essential for improving educational quality in vocational high schools (SMK), particularly in responding to rapid industrial and technological changes. This study investigates the direct and indirect effects of digital leadership, professional learning community (PLC), proactive personality, knowledge sharing, and creative self-efficacy on teacher innovation among civil servant teachers in public vocational schools in Depok City, Indonesia. Using a quantitative approach, data were collected from 158 teachers selected through proportional random sampling and analyzed through path analysis and SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management). The findings indicate that all variables positively contribute to teacher innovation, with knowledge sharing emerging as the strongest predictor, followed by proactive personality and creative self-efficacy. In addition, knowledge sharing and creative self-efficacy serve as important mediating mechanisms that strengthen the relationships between organizational and individual factors and teacher innovation. The SITOREM analysis further identified priority areas requiring improvement and indicators that should be maintained. These findings underscore the importance of integrating organizational, social, and psychological dimensions to enhance teacher innovation. The study provides both theoretical contributions through an integrated model and practical implications for educational policymakers, school leaders, and teacher professional development initiatives.